Análisis e Interpretación de los Estados Financieros de la Cooperativa de Ahorro y Crédito "Cristo Rey”, período 2022- 2023. - Masache Lapo, Liliana Maribel (2025)
The work called Analysis and Interpretation of the Financial Statements of the Savings and Credit Cooperative “Cristo Rey” 2022-2023 period, was developed with the purpose of evaluating the economic situation of the cooperative under study. In order to fulfill the objectives of this work, the basic documentation was requested, and then the vertical and horizontal method was applied to establish the financial and economic structure in percentage terms of each account, as well as possible variations of increase or decrease in the figures of the financial statements. On the other hand, for the interpretation of the results, the information gathering technique was used; in this sense, the explanatory notes corresponding to the financial statements for the 2022-2023 period were requested, in order to understand and argue the reasons behind the variations presented in the analysis applied. We continued with the calculation of financial indicators established by the Superintendency of Popular and Solidarity Economy, which allowed us to analyze the entity's economic and financial performance. These results, reflected in the traffic light analysis, led to the conclusion that the cooperative has a critical state in the recovery of its loan portfolio, due to evident increases in delinquency in its credit lines, since it exceeds the standards established by the regulatory agency SEPS. Finally, a financial analysis report was issued, which presents the results of the most representative accounts of the financial statements, thus providing conclusions and some recommendations that will help in the correct decision making process.